Correlation between behavioral and dietary factors and trends in esophageal cancer mortality in key rural areas of four Chinese provinces from 2008 to 2021: a surveillance data analysis - Chuchu WEI; Yarong HAN; Xiaoying YANG; Xuefei FENG; Xiangyi RUI; Baohua WANG (Zhongguo gonggong weisheng, 2025)
ObjectiveTo analyze the trends in esophageal cancer mortality and its influencing factors in key rural areas of four Chinese provinces from 2008 to 2021, and to explore the correlation between esophageal cancer mortality and behavioral and dietary factors, providing a reference for the prevention and control of esophageal cancer in rural China. MethodsBased on the National Mortality Surveillance Database from 2008 to 2021 and data from three surveys on tumors and behavioral risk factors conducted in 2013, 2016, and 2019 among residents in key rural areas of Jiangsu, Anhui, Shandong, and Henan provinces, Joinpoint 5.2.0 software was used to calculate the average annual percentage change (AAPC) and analyze the temporal trends of the age-standardized mortality rate of esophageal cancer in the Chinese population (referred to as the Chinese standardized mortality rate). The chi-square test for trend was used to analyze the temporal trends of behavioral and dietary factors. Panel models were established using Stata 16 software to analyze the correlation between behavioral and dietary factors and esophageal cancer mortality. ResultsThe age-standardized mortality rates (per 100 000) of esophageal cancer in key rural areas of the four provinces from 2008 to 2021 were 40.55, 36.30, 33.99, 29.65, 27.74, 26.80, 25.11, 22.76, 22.81, 19.73, 18.95, 18.12, 17.53, and 15.19, respectively, showing a decreasing trend overall (AAPC = -6.76, P < 0.001), declining from 40.55/100 000 in 2008 to 15.19/100 000 in 2021. The results of the three surveys showed that the current smoking rate, drinking rate, dietary habits (fast eating, preference for salty tastes, preference for hot food, preference for dry and hard food), and the intake frequency of some foods (pickled and salted fish, chili peppers, meat, aquatic products, and soy products) all decreased in the key rural areas of the four provinces (P < 0.001). The rates of high body mass index (BMI), insufficient physical activity, and the intake frequency of some foods (rice and rice products, fresh vegetables, fresh fruits, dairy products, and garlic) all increased (P < 0.001). Drinking rate (β = 0.51, P = 0.036), high BMI rate (β = 0.34, P = 0.041), intake frequency of pickled and fermented bean curd (β = 1.46, P = 0.010), and garlic intake frequency (β = 0.16, P = 0.025) were positively correlated with esophageal cancer mortality; while the intake frequency of rice and rice products (β = -0.21, P = 0.001), chili peppers (β = -0.35，P < 0.001) was negatively correlated with esophageal cancer mortality. ConclusionsThe age-standardized mortality rate of esophageal cancer in key rural areas of the four provinces in China showed a downward trend from 2008 to 2021. Drinking rate, high BMI rate, and the intake frequency of certain foods (pickled and fermented bean curd, garlic, rice and rice products, and chili peppers) were associated with esophageal cancer mortality.